Sunni Historiographical Orientation in the Sīrah Nabawiyah Curriculum at Ma’had Aly Sa’iidusshiddiqiyah Jakarta - Muhamad Abror; Imam Subchi (Mimbar Agama Budaya, 2026)
This article examines how Sunni historiography is taught through the sīrah nabawiyah curriculum at Ma’had Aly Sa’iidusshiddiqiyah Jakarta, a pesantren-based higher education institution specializing in Prophetic biography. Drawing on Paul Ricoeur’s concept of historiography as a “textual operation,” the study analyzes syllabi and seven prescribed textbooks (2023–2027) as institutional instruments that transmit and filter Sunni collective memory. Data were collected through textual analysis, short semi-structured interviews with curriculum implementers, thematic coding, and focused takhrīj of selected reports. The findings show that 62 of 160 credits (≈39%) are devoted to sīrah studies, indicating the centrality of Prophetic history in shaping Sunni identity. The curriculum favors a linear historical narrative, a moral-theological framework, and reverence for authoritative Sunni scholars and transmitters. A notable example is the treatment of Razīyyat Yawm al-Khamīs, a significant historical report that appears in only one of the seven prescribed textbooks despite its prominence in classical sources. This suggests institutional selectivity regarding reports sensitive to Sunni–Shiʿi historiographical debates. The study argues that contemporary pesantren higher education sustains Sunni historical narratives primarily through curricular control over what is taught and reproduced as orthodox knowledge. It concludes by advocating greater curricular diversity through new theoretical frameworks and critical methodologies.